Toxicity Assessment of a No-Pain Pharmacopuncture Extract Using a Standard Battery of In Vitro Chromosome Aberration Tests - Ji Hye Hwang (Korean Pharmacopuncture Institute, 2024)
Objectives: Genotoxicity is evaluated through a chromosomal aberration test using cultured mammalian cells to determine the toxicity of no-pain pharmacopuncture (NPP), which has recently been used to treat musculoskeletal pain disorders in Korean medical clinical practice.Methods: An initial test was performed to determine the dosage range of the NPP, followed by the main test. In this study, NPP doses of 10.0, 5.0, and 2.5%, and negative and positive controls were tested. An in vitro chromosome aberration test was performed using Chinese hamster lung cells under short-term treatment with or without metabolic activation and under continuous treatment without metabolic activation.Results: Compared with the saline negative control group, NPP did not significantly increase the frequency of chromosomal abnormalities in Chinese hamster lung cells, regardless of the presence or absence of metabolic activation. Additionally, the number of cells with structural chromosomal abnormalities was significantly higher in the positive control group than that in the negative control group that received saline.Conclusion: Based on the above results, the chromosomal abnormality-producing effect of NPP was determined to be negative under these test conditions.